Endoscopy findings in patients on dual antiplatelet therapy following percutaneous coronary intervention. Issue 1162 (20th April 2021) - Galusko, Victor; Protty, Majd; Haboubi, Hasan N; Verhemel, Sarah; Bundhoo, Shantu; Yeoman, Andrew D
Abstract: Purpose of study: This study examines the associations between dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) and gastrointestinal bleeding (GIB), to explore possible predictors of outcomes. Study design: Retrospective analysis of 3342 patients who underwent PCI between 1 August 2011 and 31 December 2018 in a single centre was carried out. Oesophagogastroduodenoscopies (OGDs) for patients 12 months post-PCI were analysed. Results: Blood loss occurred in 2% of all (3342) patients post-PCI within 12 months. 128 patients (63% male, mean age (SD) of 69.8 (10) years) who had PCI subsequently underwent an OGD within 12 months of the index PCI procedure. GIB occurred within the first 30 days of DAPT in 36% (n=13/36) of cases. There were no thrombotic events associated with cessation of one antiplatelet agent. Increased age, haemoglobin (Hb) ≤109 g/L and Glasgow-Blatchford score ≥8 were associated with increased 12-month mortality. An Hb drop of ≥30 g/L was a sensitive and specific marker for significant pathology and evidence of bleeding on OGD (sensitivity=0.83, specificity=0.81). Conclusions: GIB bleeding occurred infrequently in the patients post-PCI on DAPT. Risk assessment scores (such as Glasgow-Blatchford and Rockall scores) are useful tools to assess the urgency of OGD and need for endoscopic therapy.